Departemen Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro - Bangkit Ardhana Riyan Amukti; Raden Djoko Sampurno (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze how the impact of board of director’s characteristics (size, independence and gender percentage) on firm’s performance measured using Return on Asset (ROA), with sales growth and leverage as a control variable. Sample used in this study are 22 companies that are listed on LQ-45 index during 2016-2021 consecutively, with a total of 132 data observations. The analytical method used in this study is panel data regression with Random Effect Model (REM). The results of this study shows that board of director’s independence has a positive and significant effects on ROA. Meanwhile size and percentage gender of board of director doesn’t give a significant effect on ROA, showing that both of these variables are not the effective corporate governance mechanism to enhance the firms’ performance